Використання вторинного ресурсного потенціалу фармацевтичних відходів зі скла у виробництві керамічної плитки - Самойленко, Наталія Миколаївна; Щукіна, Людмила Павлівна; Баранова, Антоніна Олегівна (НТУ "ХПІ", 2018)
Охарактеризовані екологічні особливості фармацевтичних відходів зі скла (ФВС), основною складовою яких є використані ампули (ВА). Визначена екологічна необхідність вилучення та знешкодження залишків фармацевтичних речовин з ВА при їх утилізації. Проаналізовані ресурсні можливості використання ВА у якості вторинної сировини при виробництві керамічної плитки. Для обґрунтування екологічної доцільності та ресурсної цінності використання ВА в процесі виробництва керамічної плитки експериментально визначений хімічний склад та фізико - хімічні характеристики відходів.

The article describes ecological aspects of pharmaceutical glass wastes. It is determined that the greatest negative impact on the environment components has wastes containing pharmaceutical residue. It was analyzed that pharmaceutical glass wastes mainly consist of used ampoules (UAs).The ecological necessity of taking away and disposing residues of pharmaceutical substances from UAs by their disposal is determined. The resource possibilities of using UAs as the secondary material in production of ceramic tiles is analyzed. Monitoring of the formation and accumulation of a mixture of ampoules in the therapeutic hospital department was carried out. The mixture consisted of ampoules containing remnants of solutions of various pharmaceuticals. To substantiate the ecological practicability and resource valuation of waste used in the process of ceramic tile production, the chemical composition and physicochemical characteristics of the mixture of UAs were experimentally determined. The chemical composition and physical and chemical characteristics of wastes are experimentally determined to justify ecological expediency and waste recoverability of UAs during ceramic tiles production. The experimentally determined values of the characteristic temperature parameters and the temperature coefficient of linear expansion of the ampoule glass mixture confirm this conclusion.
The use of secondary resource potential of pharmaceutical waste from glass in the production of ceramic tiles
Keywords: екологічна безпека; ресурсна цінність; використанні ампули; медичне скло; температура; environment safety; waste recoverability